Polysaccharides of St. John's Wort Herb Stimulate NHDF Proliferation and NEHK Differentiation via Influence on Extracellular Structures and Signal Pathways - S. Abakuks; A. M. Deters (Hindawi Limited, 2012)
St. John's Wort herb extracts often contain undesirable or volitional polysaccharides. As polysaccharides exhibit structure-dependent biological functions in the present study water-soluble polysaccharides were extracted from herb material, fractionated by anion exchange chromatography into four main polysaccharide fractions (denominated as Hp1, Hp2, Hp3 and Hp4) and characterized by HPAEC-PAD, CE, IR and GC-MS. Biological activity on human skin keratinocytes and fibroblasts was assessed by investigation of their effect on proliferation, metabolism, cytotoxicity, apoptosis and differentiation. The underlying mechanisms were investigated in gene expression studies. Polysaccharide fraction Hp1 was mainly composed of β-D-glucose. Hp2, Hp3 and Hp4 contained pectic structures and arabinogalactan proteins varying in composition and quantity. Polysaccharides of Hp1 induced the keratinocyte differentiation by inhibiting the gene expression of the epidermal growth factor and insulin receptor. While the collagen secretion of fibroblasts was stimulated by each polysaccharide fraction only Hp1 stimulated the synthesis. The fibroblast proliferation was reduced by Hp1 and increased by Hp4. This effect was related to the influence on genes that referred to oxidative stress, metabolism, transcription processes and extracellular proteins. In conclusion polysaccharides have been shown as biologically active ingredients of aqueous St. John's Wort extracts with a relation between their structural characteristics and function.